Antonym Used in Translating by English Department Students of STKIP PGRI Sumatera Barat - Edwar Kemal (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2016)
The research investigated the using of antonym used by English Department Students of STKIP PGRI West Sumatra onBasic Translation class Academic Year 2013/2014. The research was focused on types of antonym used on translation. The theoriesused were Hu (2001) which was about types of antonym and Hymes which was related to context. The method of the research usedwas descriptive. The researcher presented and explained the data based on the existing phenomenon on the translation class.Technique of data collection was non participant observation in which the researcher did not involve on data occurrence. The resultsshow that student’s translation on antonym have many mistakes whether on the type of gradable, complementary and converseantonymy. Many students uses the wrong opposite.